National Innovation Capacity and Economic Growth Go Side by Side - Yassir Mahmood; Salma Mukhtar; Zulfiqar Hussain Awan; Javeria Islam; Qurat-ul-Ain (Journal of Management Practices, Humanities and Social Sciences, 2021)
This research presents an empirical examination of innovation capacity as a source of incentive for economic growth. This work introduces a novel framework by incorporating availability of latest technology, quality of management schools, intellectual property protection and intensity of local competition as the important antecedents of innovation capacity. Furthermore, it is also proposed that innovation capacity results in the outcome of economic growth of a country. Based on the previous literature five hypotheses were posed. The study utilized secondary data for 151 countries from year 2012 t0 2016 extracted from Global Information Technology Reports (GITR). The GITR is a special project of the World Economic Forum (WEF) that is published annually. Descriptive statistics and Fixed Effect Model were used to examine the hypothesized relationships and generate results. Analyses of data concluded that the entire hypotheses were approved. As use of latest technology, quality management schools, protection of intellectual property and healthy local competition enhances the level of national innovation capacity which leads to higher economic growth. These findings have important implications for research and practice as a country can contribute in economic growth by enhancing its innovation capacity.